Evolutionary and genetic implications of sequence variation in two nonallelic HLA-DR beta-chain cDNA sequences. - Curtsinger, J M (1987)
Most HLA haplotypes carry two expressed DR beta-chain genes; in the DR4 haplotype, the polymorphic locus has been called DR beta 1 and the apparently nonpolymorphic locus has been called DR beta 2. We have isolated nearly full-length DR beta-chain cDNA clones representing each of these two loci from a cell line homozygous for DR4 and Dw4. The clones have been sequenced and the sequences compared with published DR beta cDNA sequences derived from other haplotypes. A comparison of our sequences with other published cDNA sequences did not allow assignment of these other sequences to either the beta 1 or beta 2 locus. Comparison of our DR4 beta 1 sequence with DR beta 1 sequences isolated from other DR4-positive cells suggests that the alleles of DR4 beta 1 may have recently diverged from a common ancestor. The apparent lack of polymorphism of DR beta 2 may in part be a reflection of this recent divergence.